THE ROLE OF THIOL GROUPS IN THE EXPRESSION OF THE ACTIVITY OF ARGINASE I AND II ISOENZYMES (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
There are some aspects of the proteins «self-organization» that are not well studied, understanding the relationship between conformational folding linked with the formation of a disulfide bond is important and challenging from both biophysical and biochemical perspectives. In the studies, an attempt was made to elucidate the role of thiol groups in maintaining of native conformation and activity of arginase I and II of various organ origins. It was identified that depending on the stage of enzyme reactivation and the stability of the conformational state of the formed oligomers, para-chloromercuribenzoate affects the «self-organized» oligomers in different ways.
Keywords: reversible inactivation; “self-organized”; arginase I; arginase II; para-chloromercuribenzoate (PCMB); chimeric oligomers